Experience of Indonesian Working Mothers during Covid-19 Pandemic - Fariza Yuniar Rakhmawati (Perhimpunan Intelektual Muslim Indonesia, 2022)
Indonesia is in a state of emergency related to the Covid-19 pandemic which has brought major disruptions to social and economic aspects, including in the family. When schools and daycare facilities are closed due to the Covid-19, working mothers faced professional problems in balancing work and family duties. This research aims to understand the motherhood experience of Indonesian working mothers in the Covid-19 pandemic. The study was conducted to collect in-depth interview data with a semi-structured scale on six working mothers in various fields. The results showed that the strain of Indonesian working mothers escalates during the Covid-19 pandemic. Working mothers are finding it challenging to divide their time and energy between employment and childcare. They felt guilty for their children because they prioritized working rather than parenting. They also experience burnout in the form of physical and emotional exhaustion with professional obligations and child caretaking. The mothers’ emotional turbulence may lead to children maltreatment. However, some mothers reported their work and motherhood dynamic can be resolved with a good support system, particularly from husband.